2008
DOI: 10.1021/ja802486q
|View full text |Cite
|
Sign up to set email alerts
|

Application of Solid-State35Cl NMR to the Structural Characterization of Hydrochloride Pharmaceuticals and their Polymorphs

Abstract: Solid-state (35)Cl NMR (SSNMR) spectroscopy is shown to be a useful probe of structure and polymorphism in HCl pharmaceuticals, which constitute ca. 50% of known pharmaceutical salts. Chlorine NMR spectra, single-crystal and powder X-ray diffraction data, and complementary ab initio calculations are presented for a series of HCl local anesthetic (LA) pharmaceuticals and some of their polymorphs. (35)Cl MAS SSNMR spectra acquired at 21.1 T and spectra of stationary samples at 9.4 and 21.1 T allow for extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
178
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(184 citation statements)
references
References 55 publications
6
178
0
Order By: Relevance
“…39,132,[134][135][136][137][138][139][140] DFT calculations were completed using the CASTEP software package 147 (see Experimental Section for details). Molecular systems involved in strong intermolecular hydrogen-bonding interactions typically require structural optimization prior to calculation of the NMR parameters.…”
Section: Plane-wave Dft Calculations Of Nmr Interaction Tensors Planmentioning
confidence: 99%
See 1 more Smart Citation
“…39,132,[134][135][136][137][138][139][140] DFT calculations were completed using the CASTEP software package 147 (see Experimental Section for details). Molecular systems involved in strong intermolecular hydrogen-bonding interactions typically require structural optimization prior to calculation of the NMR parameters.…”
Section: Plane-wave Dft Calculations Of Nmr Interaction Tensors Planmentioning
confidence: 99%
“…Furthermore, it has been recently demonstrated that 35 Cl SSNMR can provide important structural information about the chlorine sites in different polymorphic forms in APIs, including the nature of the hydrogen bonding environments and impurity phases, in reduced experimental times compared to conventional pXRD and 13 C SSNMR experiments. 24,32,[39][40][41] For further reading on the use of SSNMR to characterize pharmaceutical compounds, we refer readers to recent reviews by Vogt and Monti et al [42][43][44] Given the ubiquity of nitrogen in functional groups such as amines, amides and numerous heterocycles, and the importance of intermolecular hydrogen-bonding interactions of nitrogen in solid APIs, the naturally occurring NMR-active nitrogen nuclei, 14 [55][56][57][58][59][60][61][62] and pharmaceuticals. 27,63-69 14 N nuclear quadrupole resonance (NQR) spectroscopy has also recently been applied, with some success, to a variety of APIs for purposes of quantification and polymorph differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Studying the structural profile of lidocaine and its salt forms will help in optimizing the formulation and drug delivery method to achieve maximum efficacy and minimal side effects. The interesting pharmaceutical [25][26][27][28][29] and structural [19,30,31] properties of lidocaine hydrochloride have prompted the present study of its conformational profile and vibrational, 1 H and 13 C NMR spectra. The predominant structure of lidocaine hydrochloride monohydrate was characterized by X-ray crystallography as fully hydrogen bonded with adjacent cations linked by water molecules in chains.…”
Section: Resultsmentioning
confidence: 99%
“…The predominant structure of lidocaine hydrochloride monohydrate was characterized by X-ray crystallography as fully hydrogen bonded with adjacent cations linked by water molecules in chains. The chains are reported to be joined in pairs by chloride ions that bind NH + and H 2 O moieties in different chains [30,31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation